DESCRIPTION OF SALIVA MELATONIN LEVELS IN GINGIVITIS PATIENTS AT RSGM UNJANI CIMAHI INDONESIA - Andi Supriatna; Tichvy Tammama; Fahira Salma Khoirunnisa (Journal of Health and Dental Sciences, 2023)
Periodontal disease is a dental and oral disease that often occurs in Indonesian society. According to Riskesdas in 2018, the Prevalence of dental and oral diseases in Indonesia was 57.6%, with most cases being dental caries and periodontal disease, while according to Purwakarta Health Profile in 2017, the periodontal disease prevalence in West Java was 85.6%. One of the most common periodontal diseases in Indonesia is Gingivitis. According to Riskesdas, in 2018, the Prevalence of Gingivitis in Indonesia reaches 74%. Gingivitis is an inflammatory process in the gum tissue of the oral cavity. The body has a hormone that acts as an anti-inflammatory and antioxidant in periodontal diseases, namely melatonin. melatonin hormoneill decrease if there is inflammation in the body, increased free radicals, bone damage, immune system disorders, oxidative stress, and circadian rhythm disorders. This study aimed to describe the melatonin level in gingivitis patients' saliva. This study used cross-sectional quantitative descriptive research as its methodology. The level of melatonin in the saliva is low if <2 pg/ml, normal: 2-4pg/ml, and high: >4pg/ml. The results showed that the mean melatonin level in the saliva of gingivitis patients at RSGM Unjani was 13.8 pg/ml, with a minimum melatonin level of 6.9 pg/ml and a maximum of 48.5 pg/ml. The results of the research and data analysis concluded that the level of melatonin in the saliva of patients with Gingivitis at RSGM Unjani is elevated, which is caused by various factors that affect melatonin levels. DOI : 10.54052/jhds.v3n1.p79-88